Effect of Thickness and Compaction Degree of Overburden Soil on Radon Reduction for Uranium Tailings Reservoir. (22nd March 2021) - Dai, Xingwang; Chen, Yifan; Chen, Yan; Wang, Hong; Li, Xiangyang; Hong, Changshou; Liu, Yong
Abstract : The thickness and compaction degree of the overburden soil on the beach of the uranium tailings reservoir has an important influence on the radon reduction rate. A theoretical model of radon exhalation is established and an experimental device is designed. The main results are as follows. (1) The radon reduction rate increases with the increase of thickness. When the soil compaction degree is 85.5%, 90.2%, and 94.8%, the radon reduction efficiency increases significantly when the thickness increases from 5 cm to 10 cm, and when the soil thickness is over 10 cm, the increase of radon reduction efficiency tends to be stable. When the compaction degree is 80.9%, the radon reduction rate always increases obviously with the increase of the thickness of the overburden soil, but the increase rate shows a downward trend. (2) The radon reduction rate increases gradually with the increase of compaction degree, and the increasing trend becomes less obvious when the compaction degree is more than 85.5%. Besides, the effect of the change of soil compaction on radon reduction rate decreases with the increase of soil thickness. The calculation formulas about the effect of thickness and compaction degree on radon reduction rate can guide the design and construction of radiation protection of uranium tailings reservoir.